A new function for the Fragile X Mental Retardation Protein in the regulation of PSD-95 mRNA stability - Zalfa, Francesca (2007)
Fragile X Syndrome results from loss of the Fragile X mental retardation protein (FMRP), an RNA-binding protein regulating a variety of cytoplasmic mRNAs. FMRP regulates mRNA translation and has been suggested to play a role in mRNA localization to dendrites. We report a third cytoplasmic regulatory function for FMRP – control of mRNA stability. We find in mice that FMRP binds, in vivo, the mRNA encoding PSD-95, a key molecule regulating neuronal synaptic signalling and learning. This interaction occurs through the 3′ untranslated region of the PSD–95 mRNA, increasing message stability. Moreover, stabilization is further increased by mGluR activation. While we also find that the PSD–95 mRNA is synaptically localized in vivo, localization occurs independently of FMRP. Through our functional analysis of this FMRP target we provide evidence that misregulation of mRNA stability may contribute to the cognitive impairments in Fragile X Syndrome patients.